Reduced training duration effects on aerobic power, endurance, and cardiac growth - Hickson, R. C.; Kanakis, C.; Davis, J. R.; Moore, A. M.; Rich, S. (Journal of Applied Physiology, 1982)
Thirteen subjects participated in an exercise program of bicycling and running 40 min/day, 6 days/wk. After 10 wk they continued to train either 26 of 13 min/day for an additional 15 wk. Intensity and frequency for the additional 15 wk remained the same as the last 3 wk of training. This study was undertaken to gain further insights into whether the increases in maximum uptake (VO2 max), endurance, and cardiac size can be maintained with reduced training durations. The average increases in VO2 max in response to 10 wk training were between 10 and 20% during the bicycle and treadmill testing. After reduced training, VO2 max continued to remain at the training levels in both groups. Short-term endurance (approx 5 min) was also maintained by both groups. Long-term endurance (2 h or more) remained the same in the 26-min group but decreased significantly (10%, 139-123 min) in the 13-min group. Calculated left ventricular mass increased 15-20% after training and remained elevated after reduced training in both groups. We conclude that it is possible to maintain almost all of the performance increases with up to a two-thirds reduction of training duration. Nevertheless, the data provide initial evidence that all aspects of the endurance-trained state may not be regulated uniformly in reduced training, particularly since VO2 max and short-term endurance were maintained, but long-term endurance decreased in the 13-min group.